(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
Wild thyme leaves Thymus SP collected from areas different regions in Jableh and Lattakia countryside in Lattakia governorate were studied to determine the chemical compounds in its oil. A mixture of (42) compounds was detected in the leaf oil, In order to find out the components and determine their proportions, gas chromatography technology linked to mass spectrometry (GC/MS) was used. The leaves were collected from 5 different locations, then mixed and a representative sample was taken from them to investigate the type of compounds present in the sample oil. The leaves were cleaned, dried and ground with a blender, and then the oil was extracted by Clavenger distillation apparatus. The results showed that the existing compounds follow multiple functional groups, including: hydrocarbons, terpenes, phenols, alcohols, ketones, fatty acids and esters,..... The highest percentage was recorded for the group of phenols, with a percentage of (36.46%), followed by the group of terpenes, with a percentage of (21.77%). the alcohol group its percentage was (1.51%), while the percentage of fatty acids was ((1.23%), in addition to the ester group which amounted to (0.07%), and the ketone group and its percentage was (0.03%). And based on previous studies that talked about the various biological efficacy of many compounds present in wild thyme leaf oil, including (antibiotics for various pests, antioxidants...etc), Showing the importance of wild thyme products in the health (pharmaceutical industry) and agricultural fields (finding pesticides of natural plant origin). The study was carried out in the year (2022) in the laboratories of the Higher Institute for Marine Research and the Plant Protection Department, in the Faculty of Agriculture, Tishreen University.